Elevated Molybdenum Concentrations in Soils Contaminated with Spent Oil Lubricant - Yakasai, Hafeez Muhammad; Rahman, Mohd Fadhil; Yasid, Nur Adeela; Ahmad, Siti Aqlima; Halmi, Mohd Izuan Effendi; Shukor, Mohd Yunus (Journal of Environmental Microbiology and Toxicology, 2017)
Molybdenum is an essential trace element of which its pollution due to excessive levels are increasingly reported worldwide. One of the most important usage of molybdenum is as an engine lubricant. Pollution of spent oil lubricant due to indiscriminate dumping of the waste is an important source of molybdenum pollution. In this study, soil samples from various locations in Malaysia were taken from sites which are visible with the dumping of spent oil lubricant and were tested for the presence of soluble and insoluble molybdenum content. The highest concentrations of Mo found for both of the aqua regia digested and ammonium extracted soil sample were at 35.27 and 17.86 mg/Kg soil, respectively. The percentage of ammonium acetate (soluble) extractable Mo to total Mo measured as the aqua regia digested sample was also the highest at 50.64%. The results indicated an excessive content of molybdenum on these soils which warrant remediation process.